2008
DOI: 10.1115/1.2885079
|View full text |Cite
|
Sign up to set email alerts
|

Spherical Bistable Micromechanism

Abstract: A new micromechanism, the spherical bistable micromechanism (SBM), is described. The SBM has several advantageous features, which include two stable positions that require power only in transitioning from one position to the other; robustness against small disturbances; and a compact footprint and an output link with a stable out-of-plane orientation. The SBM may be useful in applications such as 2D optical mirror arrays or in erecting out-of-plane structures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…By definition, a spherical mechanism is one in which all axes of rotation intersect at a common point, as illustrated in figure 3. Bistable spherical compliant mechanisms have been considered previously [27,28], but these mechanisms had fewer links than are found in a waterbomb base. Nevertheless, some of the concepts used in these investigations are applicable to the current study.…”
Section: Descriptionmentioning
confidence: 99%
“…By definition, a spherical mechanism is one in which all axes of rotation intersect at a common point, as illustrated in figure 3. Bistable spherical compliant mechanisms have been considered previously [27,28], but these mechanisms had fewer links than are found in a waterbomb base. Nevertheless, some of the concepts used in these investigations are applicable to the current study.…”
Section: Descriptionmentioning
confidence: 99%
“…The design is based on a bistable four-bar mechanism consisting of three relatively rigid links (blue, green, and cyan in Figure ) and one compliant link (red in Figure ). Analogous bistable four-bar mechanisms have previously been implemented in MEMS applications. , Here, the three relatively stiff links consist of a 10-helix bundle (hb), and the compliant link is a 6-hb of dsDNA. At either end of the compliant 6-hb, the cross section is increased to a 10-hb to allow appropriate attachment to other components.…”
mentioning
confidence: 99%
“…Analogous bistable four-bar mechanisms have previously been implemented in MEMS applications. 43,44 Here, the three relatively stiff links consist of a 10-helix bundle (hb), and the compliant link is a 6-hb of dsDNA. At either end of the compliant 6-hb, the cross section is increased to a 10-hb to allow appropriate attachment to other components.…”
mentioning
confidence: 99%
“…Bowen et al 19 presented a position analysis of coupled spherical mechanisms found in action origami. Lusk and Howell 20 described a new micro-mechanism, namely, the spherical bistable micromechanism. Callegari et al 21 described the design of a robotic wrist that can perform spherical motions.…”
Section: Introductionmentioning
confidence: 99%